Time between onset of symptoms and definitive treatment in children with acute appendicitis: How it affects length of hospital stay? - Anastasia Dimopoulou; Amalia Yfanti; Theodoros Argyropoulos; Eleni Evaggelou; Dimitra Dimopoulou; Konstantina Dimopoulou; Emmanouil Iakomidis; Paraskevi Feizidou; Nikolaos Zavras (Wolters Kluwer Medknow Publications, 2022)
Purpose: Any delay in treatment of acute appendicitis (AA) could lead to complications increasing morbidity and length of hospital stay (LHS). The aim of this study was to determine the time interval between onset of symptoms and seeking medical attention and definitive treatment in children with AA and its impact on LHS. Materials and Methods: A prospective study was conducted from December 2017 to March 2018. All patients diagnosed with AA and who underwent surgical procedure were enrolled. A questionnaire leaflet completed by parents was used to collect clinical data and information about seeking medical attention and children's management. Time was divided into six different intervals (1-2 h, 3-6 h, 7-12 h, 13-24 h, >24 h and >48 h) to estimate the time between onset of symptoms and seeking medical attention and time between hospital admission and surgical procedure. LHS was recorded. Results: During the study period, 125 children were enrolled. Over half of the patients sought for medical assistance relatively soon (3-12 h) after the onset of symptoms, whereas 17.6% sought late healthcare (>24 h). The time between the medical examination and surgical procedure was <24 h in approximately 80% of the children. LHS was affected by time between onset of symptoms and seeking medical attention and time between medical examination and surgical procedure (P = 0.001 and P = 0.017, respectively). Conclusions: The majority of the children with AA admitted to hospital were treated relatively soon after the onset of symptoms. However, a significant proportion of children delayed to seek medical advice and undergo appendectomy, increasing LHS.